2014
DOI: 10.1038/nature13073
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR-25 improves cardiac contractility in the failing heart

Abstract: Heart failure is characterized by a debilitating decline in cardiac function1, and recent clinical trial results indicate that improving the contractility of heart muscle cells by boosting intracellular calcium handling might be an effective therapy2,3. microRNAs (miRs) are dysregulated with heart failure4,5 but whether they control contractility or constitute therapeutic targets remain speculative. Using high throughput, functional screening of the human microRNAome, we identified miRs that suppress intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
288
3
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 387 publications
(307 citation statements)
references
References 43 publications
9
288
3
7
Order By: Relevance
“…miR-25 is known to be important in several types of cancer, including hepatocellular carcinoma, and colon, gastric and lung cancer (34)(35)(36). miR-25 has been indicated to be involved in various cellular processes, including cell proliferation, apoptosis and the release of cytokines (37)(38)(39)(40). Esposito et al (36) demonstrated that miR-25 was reduced in anaplastic thyroid carcinomas, and ectopic expression of miR-25 suppressed the proliferation and colony formation of anaplastic thyroid carcinoma cells via the induction of G 2 /M-phase cell cycle arrest (36).…”
Section: Discussionmentioning
confidence: 99%
“…miR-25 is known to be important in several types of cancer, including hepatocellular carcinoma, and colon, gastric and lung cancer (34)(35)(36). miR-25 has been indicated to be involved in various cellular processes, including cell proliferation, apoptosis and the release of cytokines (37)(38)(39)(40). Esposito et al (36) demonstrated that miR-25 was reduced in anaplastic thyroid carcinomas, and ectopic expression of miR-25 suppressed the proliferation and colony formation of anaplastic thyroid carcinoma cells via the induction of G 2 /M-phase cell cycle arrest (36).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-miR-25 delivery restores cardiac function and improves survival. 36 Also, miR-24 regulates calcium homeostasis through Junctophilin-2 repression, which results in decreased efficiency of excitation-contraction (E-C) coupling in cardiomyocytes. 37 In a recent paper, Melman et al provided evidence that increased cardiac miR-30d expression has a significant impact on responses to cardiac resynchronization therapy (CRT), and that plasma levels of miR-30d may correlate with responsiveness to CRT in heart failure patients.…”
Section: Heart Failurementioning
confidence: 99%
“…Many pathologies have been linked to aberrant miRNA expression patterns, including cancer, metabolic disorders, heart failure and neurological diseases [1014]. To study miRNA functioning in biological systems, potent and specific miRNA inhibitors that can be efficiently delivered in the target cell are desired.…”
Section: Introductionmentioning
confidence: 99%